The Approach of D. Trump's Administration to the Middle East Settlement - A. V. Krylov (Международная аналитика, 2018)
Immediately after D. Trump was elected President of the United States in November 2016, he announced that he had his own plan for the Palestinian-Israeli conflict settlement. D. Trump promotes this plan as "the deal of the century", which will lead to the long-awaited peace in this long-suffering region of the Middle East. However, as soon as several media sources started publishing certain details of this plan with reference to reliable sources, it immediately gained sharp criticism from many well-known politicians. The Palestinian side officially announced that the initially biased new American initiatives exclude the USA mediation in the negotiation process on the Middle East settlement. For this reason, the abovementioned "Trump's plan" has not yet been officially announced.In the course of the recent business trip to the West Bank the author of this article managed to meet several well-informed representatives of the Palestinian team, who had earlier participated in the negotiations on the settlement of the conflict with the Israeli side. Basing on the information received, the author of this article analyzes the key points of D. Trump's Middle East initiative. The main conclusion of the analysis is that the widely advertised "deal of the century" died before its birth and even under strong pressure of the USA, both sides of the conflict will not agree to cooperate within the frames of the new Middle East doctrine of D. Trump.